2018
DOI: 10.1002/adtp.201800021
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐Functionalized Synthetic Dendritic Cells for T Cell Targeted Immunotherapies

Abstract: Widespread application of cytokine-based therapies is hampered by severe toxic side effects, resulting from off-target (immune) cell stimulation. This emphasizes the need for more precise targeting of cytokines to immune cells. While cytokines are generally active as soluble proteins, it is demonstrated here that synthetic mimics of immune cells based on polyisocyanopeptides (PICs), called synthetic dendritic cells (sDCs) can efficiently present immobilized cytokines to T cells, when targeted by anti-CD3 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 51 publications
(72 reference statements)
0
71
0
Order By: Relevance
“…The authors showed that the increased multivalency of the antibody‐functionalized sDCs produced a significant reduction in the threshold of T cell activation. Recently, a study showed that cytokine‐functionalized nanoworms can be used to trigger T cell responses . The PIC‐based nanoworms were decorated with IL‐2 and anti‐CD3, which stimulated T cell activation and proliferation.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…The authors showed that the increased multivalency of the antibody‐functionalized sDCs produced a significant reduction in the threshold of T cell activation. Recently, a study showed that cytokine‐functionalized nanoworms can be used to trigger T cell responses . The PIC‐based nanoworms were decorated with IL‐2 and anti‐CD3, which stimulated T cell activation and proliferation.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…Recent work with aAPCs comprising polyisocyanopeptide polymers 100-1000 nm long, functionalized with anti-CD3 and IL-2, showed that closer spacing of the anti-CD3 and IL-2 contributed to T-cell activation (Hammink et al, 2018). These aAPCs together reveal that tuning antigenic signals and spatial separations has utility and offers an advantage over biological antigen presenting cells when developing engineering solutions to scaling the production of T cells for therapeutic purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Within the NP core there is also the potential to load cytokines such as IL-2 that induce proliferation of T cells. [55,56] Copyright 2018, John Wiley and Sons and Springer Nature, respectively. [55] One desired element of this modular platform is the flexibility that supports dynamic rearrangement of the signaling cues during T cell interactions.…”
Section: Vaccines and Artificial Apcs Program Antigen Presentationmentioning
confidence: 99%